Strategi Komunikasi Pemasaran Dinas Kebudayaan dan Pariwisata Kabupaten Kudus dalam Meningkatkan Jumlah Pengunjung Museum Kretek - Reski Rosalia; Hedi Pudjo Santoso (Interaksi Online, 2018)
The research is based on the phenomenon that happened at Museum Kretek. In 2017, Museum Kretek has decline the number of the visitors, and in 2014 to 2017 Museum Kretek can’t reach the target which has been determined. The problem of this research is how can the strategy of the marketing communication that used by culture and tourism office increase the number of visitor in at museum kretek. the aim of the research is to know and evaluate the strategy of marketing communication that used by culture and tourism office in Kudus in increasing the number of visitor at museum kretek. The method that used in this research is qualitative descriptive with research method study case on the strategy of the marketing communication at Museum Kretek wich done by culture and tourism office in Kudus. To collect the data, the writer uses interview with the subject of the research and the informan and she also uses the documentation from the archives of culture and tourism office in Kudus. Based on the result and the analysis of the research with using analysis data technique, wich is matching pattern and strategy communication done by culture and tourism office in Kudus in inceasing the number of the visitor at Museum kretek can be concluded that. 1. Communicating thhe program or a near thing in the some of media as a publication and promotion. 2. Establish cooperation with internal public and external. 3. Build many communication program to make the visitor more interested. 4. Doing innovation and improvement to infrastructure at Museum Kretek. 5. Improving the human resources for better service..